Equal prioritisation does not yield lower levels of participation in physical activities than higher prioritisation. (January 2016) - Chatzisarantis, Nikos L.D.; Barkoukis, Vassilis; Yli-Piipari, Sami; Thogersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Hardcastle, Sarah; Hagger, Martin S.
Abstract: Objectives: This study examined whether individuals who assigned equal priority to physical activity and an alternative activity exhibited lower levels of participation in physical activities than individuals who assigned higher priority to physical activity than an alternative activity. In addition, we examined whether a measure of prioritisation derived from an algebraic difference index provided a rigorous test of prioritisation effects. Design: We employed a two-wave prospective design that aimed to predict physical activity participation. Method: Prioritisation, intentions and perceptions of control were measured at the first wave of data collection. After five weeks, we administered follow-up measures of behavioural conflict and physical activity participation. Results: A hierarchical regression analysis showed that although the algebraic difference index was positively associated with measures of physical activity participation, equal prioritisation did not yield lower levels of physical activity participation than high prioritisation. Conclusions: Findings suggest that equal prioritisation is not a less optimal self-regulatory strategy than high prioritisation in the domain of physical activity. Regression coefficients associated with algebraic difference indexes should be interpreted with caution and consider analyses that examine effects of component measures of prioritisation on physical activity participation. Highlights: Equal prioritisation does not yield lower levels of participation than high prioritisation. Correlations with algebraic difference indexes should be interpreted with caution. Researchers should use additive models of prioritisation.